Philosophical Features of the Conceptual Approach in the Formation of Environmental Ethics in the Process of Globalization - Z. A. Abduazimova (International Journal on Integrated Education, 2021)
Environmental ethics, as a scientific field, focuses on the preservation of natural and human beings, offers a holistic approach to the current crisis and offers a variety of approaches to addressing the specific depths of moral culture, embodies a holistic relationship between nature, society and man. Therefore, an understanding of the interrelationships between man and nature in conflicting global trends proves the importance of completely natural processes in solving this problem.